2017
DOI: 10.17221/421/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of peptide fractions derived from freshwater mussel protein using ultrasound-assisted enzymatic hydrolysis

Abstract: Dong Z., Tian G., Xu Z., Li M., Xu M., Zhou Y., Ren H. (2017): Antioxidant activities of peptide fractions derived from freshwater mussel protein using ultrasound-assisted enzymatic hydrolysis. Czech J. Food Sci., 35: 328-338.The freshwater mussel protein was hydrolysed using ultrasound-assisted enzymolysis. Ultrasound-assisted freshwater mussel protein hydrolysates (UPH) were divided into four fractions (> 10, 6-10, 3-6, and < 3 kDa) using ultrafiltration, and the fraction with the highest antioxidant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Several studies have reported that the bioactivity of peptide mixtures is largely affected by their molecular sizes and that the low-molecular-weight fractions exhibit more potent antioxidant activities, which may be due to the presence of hydrophobic amino acids in low-molecular-weight peptide. (Dong et al 2017 ). For example, low-molecular-weight whey hydrolysate peptides (0.1–2.8 kDa) have been found to be highly antioxidative and can protect lung fibroblast MRC-5 cells against H 2 O 2 -induced oxidative damage (Kong et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the bioactivity of peptide mixtures is largely affected by their molecular sizes and that the low-molecular-weight fractions exhibit more potent antioxidant activities, which may be due to the presence of hydrophobic amino acids in low-molecular-weight peptide. (Dong et al 2017 ). For example, low-molecular-weight whey hydrolysate peptides (0.1–2.8 kDa) have been found to be highly antioxidative and can protect lung fibroblast MRC-5 cells against H 2 O 2 -induced oxidative damage (Kong et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical tests to ascertain the phytochemicals of exudates revealed the presence of alkaloids, avonoids, anthraquinone, cardiac glycoside and phlorotannin's (Abdel Ghany et al 2019). Mass spectrometry analysis of banana stem extract with methanol (80%) showed the presence of many antidiabetic compounds (Dong et al 2017). Although different species of the banana stem was used for extraction with different solvents and examined for their cytotoxic activities; compounds responsible for cytotoxicity or antimitotic activity have not been identi ed or proposed yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, the amino acid composition and peptide sequence are also important determinants of antioxidant activity. Peptides of freshwater mussels with a high molecular weight were reported to show relatively high antioxidant activity due to the abundant hydrophobic amino acids [26]. Indeed, hydrophobic and aromatic amino acids are known to play important roles in the antioxidant activity of peptides [27].…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyl radical scavenging activity of peptide fractions was determined according to the methods described by Dong et al [26]. Vitamin C was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%